New records of Odonata from Argentina - Rodríguez, José Sebastián (2018)
The present paper provides new records for Zygoptera and Anisoptera collected in the central and northern regions of western Argentina (23° to 30°S latitude), including the biogeographical provinces of Puna, Monte, Chaco and Yungas. Nineteen sampling sites were visited at least once. New geographical records for 20 species are reported, including three new national records for Argentina - Gynacantha mexicana Selys, Rhionaeschna cornigera (Brauer) and Triacanthagyna caribbea Williamson - and 19 new provincial records from 17 species. Two of them involve large range expansions since they were previously known only from the east of the country, viz. Brachymesia herbida (Gundlach) and Macrothemis hemichlora (Burmeister). Other records involve moderate to small range extensions for 15 species. Photographs of diagnostic characters are given for all the species.